piRNA clusters and open chromatin structure - Yamanaka, Soichiro (BioMed Central, 2014)
Transposable elements (TEs) are major structural components of eukaryotic genomes; however, mobilization of TEs generally has negative effects on the host genome. To counteract this threat, host cells have evolved genetic and epigenetic mechanisms that keep TEs silenced. One such mechanism involves the Piwi-piRNA complex, which represses TEs in animal gonads either by cleaving TE transcripts in the cytoplasm or by directing specific chromatin modifications at TE loci in the nucleus. Most Piwi-interacting RNAs (piRNAs) are derived from genomic piRNA clusters. There has been remarkable progress in our understanding of the mechanisms underlying piRNA biogenesis. However, little is known about how a specific locus in the genome is converted into a piRNA-producing site. In this review, we will discuss a possible link between chromatin boundaries and piRNA cluster formation.